Image and signal processing : 8th International Conference, ICISP 2018, Cherbourg, France, July 2-4, 2018, Proceedings /: 8th International Conference, ICISP 2018, Cherbourg, France, July 2-4, 2018, Proceedings. (2018) - Unknown
No abstract available